Skúli Þórðarson Thorlacius on Historical Nordic Wrestling: Translation and Commentary of a Passage in Borealium veterum matrimonia (1785) - Ijäs, Antti (Mirator, 2025)
Skúli Þórðarson (Skulius Theodori) Thorlacius’s (1741–1815) monograph on the marriage rites of the ancient Nordics (Borealium veterum matrimonia, Copenhagen 1785) includes an excursus into spectacles that includes a section on wrestling (glíma). Thorlacius discusses the topic with references to contemporary traditions, saga literature, and comparisons with ancient athletics. Thorlacius’s treatise is one of the earliest scholarly treatments of historical Nordic wrestling, predating the Viking revival of the nineteenth century. For the benefit of recent surge in the interest in the study of historical martial cultures, this article makes Thorlacius’s text accessible both in its Latin original and an English translation with a commentary focusing on his sources. The edition and translation are followed by a critical appraisal of Thorlacius’s conclusions, with additional notes on the history and meaning of lausa-tök, a wrestling term attested from the early eighteenth century onwards.